2002
DOI: 10.1007/s10123-002-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

The aerobic dechlorination activities of two bacterial species isolated from a refuse dumpsite in Nigeria

Abstract: Two bacterial species isolated using enrichment culture techniques from the topsoil of a main refuse dumpsite in Nigeria were assessed for their dehalogenation potentials. The bacterial isolates were identified as belonging to the Bacillus and Pseudomonas genera. Axenic cultures of the isolates utilized monochloroacetic acid (MCA), trichloroacetic acid (TCA), trichloromethane (CHCl3) and tetrachloromethane (CCl4) as the sole source of carbon for growth up to a final substrate concentration of 0.1% (w/v). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Interestingly, debromination was much higher at 35°C than that at 30°C, although bacterial growth was slightly slower at 35 than that at 30°C. Our findings are in agreement with previous reports that the optimal temperature for aerobic dechlorination by two other bacterial species was between 30 and 35°C (Olaniran et al, 2002).…”
Section: Growth and Debromination Activity Of Ochrobactrum Sp Tsupporting
confidence: 83%
“…Interestingly, debromination was much higher at 35°C than that at 30°C, although bacterial growth was slightly slower at 35 than that at 30°C. Our findings are in agreement with previous reports that the optimal temperature for aerobic dechlorination by two other bacterial species was between 30 and 35°C (Olaniran et al, 2002).…”
Section: Growth and Debromination Activity Of Ochrobactrum Sp Tsupporting
confidence: 83%
“…This is closer to the observation in this study as only 4.69 and 6.61% loss in activities was observed for isolate SA 3 and SA 4 , respectively at pH 9.5 compared to the activities at pH 9.0. However, the optimum pH of 7.5 observed for the haloalkane activities corroborates previous findings [16,30]. The different pH optima observed for haloalkane and halocarboxylic acid activities in this study suggested the existence of different dehalogenases for the degradation of the compounds by the bacterial isolates.…”
Section: Effects Of Ph and Temperature On The Dehalogenase Activitiessupporting
confidence: 93%
“…Meanwhile, most environments in this continent are widely polluted with this group of compounds, without appropriate regulatory acts to monitor their discharge into the environment. Previously, we reported the dehalogenation potential of some bacterial isolates indigenous to contaminated sites in Nigeria [15,16]. In this study, we describe the potential of two bacteria isolated from a wastewater treatment plant in South Africa for aerobic dehalogenation of some aliphatic chlorinated compounds as well as characterizing their dehalogenase activities in an attempt to develop active bacterial consortia that may be applicable for the bioremediation of sites polluted with chlorinated hydrocarbon compounds in Africa.…”
Section: Introductionmentioning
confidence: 98%
“…The agent responsible for dechlorination of CCl 4 by strain KC is an extracellular metal chelator, pyridine-2,6-bis(thiocarboxylic acid) (PDTC) (31,33). In addition, isolates of Bacillus, Corynebacterium, and Pseudomonas that are capable of aerobic CCl 4 dehalogenation have been described, with cell extracts removing CCl 4 at the same rate as cultures (42,43).…”
Section: ؊1mentioning
confidence: 99%